2010
DOI: 10.1007/s00703-010-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

The 26 July 2005 heavy rainfall event over Mumbai: numerical modeling aspects

Abstract: The performance of the Advanced Regional Prediction System (ARPS) in simulating an extreme rainfall event is evaluated, and subsequently the physical mechanisms leading to its initiation and sustenance are explored. As a case study, the heavy precipitation event that led to 65 cm of rainfall accumulation in a span of around 6 h (1430 LT-2030 LT) over Santacruz (Mumbai, India), on 26 July, 2005, is selected. Three sets of numerical experiments have been conducted. The first set of experiments (EXP1) consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This was the case for direct model forecasts leading up to the disastrous 2011 Brisbane River and Lockyer Valley floods, which were a third of the amount actually received (van den Honert and McAneney 2011). A similar situation occurred in the disastrous 2005 Mumbai Floods (Sahany et al 2010), and in 2006 associated with one of the worst floods to affect China since 1983 (Gao et al 2009). …”
Section: Summary and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This was the case for direct model forecasts leading up to the disastrous 2011 Brisbane River and Lockyer Valley floods, which were a third of the amount actually received (van den Honert and McAneney 2011). A similar situation occurred in the disastrous 2005 Mumbai Floods (Sahany et al 2010), and in 2006 associated with one of the worst floods to affect China since 1983 (Gao et al 2009). …”
Section: Summary and Discussionmentioning
confidence: 74%
“…van den Honert and Mc Aneney (2011), for example, showed that the rainfall forecasts prior to the disastrous 2011 Brisbane River and Lockyer Valley floods in Queensland forecasted rainfall that was approximately one third of that actually received. An underestimation of extremely heavy rainfall also occurred for the disastrous 2005 Mumbai Floods (Sahany et al 2010), and the severe floods in China in 2006 (Gao et al 2009). Indeed, often the most intense rainfall in a major flood event is not sampled by even a relatively dense rain gauge network.…”
mentioning
confidence: 99%
“…The breaking of the MCS with a part going north-westward and another part moving towards Mumbai has not been documented in the previous study of Sahaney et al [41]. They used conventional methods of manually tracking low pressure systems (Figure 1 in their paper).…”
Section: Mumbai Rainfallmentioning
confidence: 91%
“…If we examine the large-scale features we note that prior to this event, monsoon was in an inactive phase from 19-22 July 2005. On 23 July a low pressure area formed over Northern Bay of Bengal, intensified into a well-marked low, and moved westward [41]. Figure 10(a) shows the set of clouds during the start of the rainfall phenomenon over Mumbai.…”
Section: Mumbai Rainfallmentioning
confidence: 99%
“…• N for the July 2005 Mumbai rainfall event [12]. The period of simulation was from July 24, 2005 18:00 hours -July 27, 2005 18:00 hours.…”
Section: B Domain Configurationsmentioning
confidence: 99%